A study on cervical cytopathology in HIV positive pregnant women in Southern part of Assam, India - Choudhury, Arun Paul; Acharyya, Tanaya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: The association between abnormal cervical cytology and HIV infection status in pregnant women was evaluated to correlate with CD4 cell count, viral load and ART compliance in HIV positive pregnant patients with the presence of ASC-US, LSIL and HSIL. Methods: Cervical samples were collected at the Antenatal Clinic of Silchar Medical College and Hospital. An Ayre’s spatula was used to collect samples from the ectocervix and a cytology brush to collect samples from the endocervix. Results: Of a total of 75 antenatal attendees, 43 were HIV positive and 32 were HIV negative. Abnormal cytology (N=26, 60.46%) was more common in HIV positive group compared to the HIV negative group (N=7, 21.87%) with a p value of <0.05. Cytological abnormalities were found to be associated with immunosuppression, defined as CD4 count <200 cells/mm3 and was also associated with high viral load(>10,000/mm3) and poor treatment follow up with ART. Conclusions: HIV positive pregnant women are more likely to have cervical lesions as compared to the HIV negative. This higher frequency of abnormal findings in PAP cytology in HIV positive pregnant women with higher viral loads suggest association between preinvasive cervical lesions and human immune deficiency.